A Study on Escherichia Coli Isolated from Urogenital Tract Infections, Emphasizing their Occurrence and Antibiograms - Nida Basharat Khan, Mehwish Shehzadi, Hira Hameed, Muhammad Feeroz Nazeer, Usman Amjad, Muhammad Rizwan, Bushra Abid, Sidra, Fidaa Aslam, Talat Sabtain (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Urinary tract infections (UTIs), which are among the most prevalent infections both in the general population and in health care facilities, are ranked second only to upper espiratory tract infections in terms of the prevalence of the disease. Methodology: Samples for the current investigation were gathered from severalprivate and public hospitals. Based on colony morphology, these samples were identified via Gramstaining and biochemical analysis. Following CLSI 2019 standards, these isolates were nexttested for antibiotic susceptibility using Kirby-disc Bauer’s diffusion assay. Results: For the presence of Escherichia coli, 48(26.6%) of the 180 sample stested negative, while 132(73.3%) test edpositive. Escherichia coli isolates were found to be highly resistant to ciprofloxacin, Amoxicillin-Clavulanic acid, Gentamicin, Ofloxacin, Piperacillin-Tazobactam, Meropenem, Imipenem, Tobramycin, Amikacin, andColistin, according to the antimicrobial susceptibility pattern. Imepenem, meropenem, amikacin,gentamicin, amoxicillin-clavulanic acid, cefixime, cefotaxime, ciprofloxacin, and cefoperazone were all highly effective against the isolates. Clinical Implication: The clinical implication of the study is to isolate the E.coli from community-acquired UTI and also to enlighten the antimicrobial resistance pattern regarding E. coli. Conclusion: Antimicrobial susceptibility testing results should be heeded when prescribing treatment for urinary tract infections to avoid the possibility of Escherichia coli’sgrowingresistancetoseveralantimicrobialmedications. Keywords: Urinary tract infections (UTIs), Antimicrobial Activities, Healthcare, Antibiotics